MODEL MANAJEMEN PENDIDIKAN KARAKTER BERBASIS INTEGRASI NILAI-NILAI RELIGIUS DAN MULTIKULTURAL - Rohmat Rohmat (Jurnal Penelitian Agama, 2019)
Securing religious and multicultural character values ​​is very important to be instilled as early as possible through education. This is due to education not only providing increased intellectual ability, but also is responsible for integrating character values ​​in students. At least there are some aspects that need to be developed in the education phase of school children including intellectual aspects, emotional aspects, social aspects, physical aspects, aspects of movement, aesthetic aspects, and moral aspects. Based on this opinion it can be seen that the cultivation of religious and multicultural character values ​​in madrasa ibtidaiyah level students needs to be done in order to realize a future generation of adults and character. On the other hand, the cultivation of multicultural values ​​is also an urgent matter to do.This study aims to find a character education management model based on the integration of religious and multicultural values ​​in MI Banyumas Regency. The research method with research and development methods. The results of the study of the character education management model based on the integration of religious and multicultural values ​​that were developed effectively for use in character education in Madrasah Ibtidaiyah. The results of the t test through the paired t test method showed that there were significant differences between the character values ​​before and after the implementation of character education in Madrasah Ibtidaiyah. These results reinforce that character education is effectively used in Madrasah Ibtidaiyah.